Bela Studio : membela anak dengan teater - Nashir, MJA, 1973-; Sutrisno, Mudji (Yogyakarta : Kepel Press, 2001)
Art performing of Bela Studio, a children's theater in Jakarta
Sumber Pustaka : p. 206-210
Keywords: Indonesian drama -- Social aspects; Children's theatre -- Indonesia -- History and criticism